Reproductive biology and pollination ecology of two edible Limnophila species in Thailand - RUNGTIP MALAIPHIS; WITTAYA PAKUM; SIRIDUANGKAMOL KAPHANG; THOTSAPORN CHANOKKHUN; NOODUAN MUANGSAN; NATAPOT WARRIT; PRAPUN TRAIYASUT; CURT HRAD BARNES; SANTI WATTHANA (Society for Indonesian Biodiversity, 2026)
Abstract. Malaiphis R, Pakum W, Kaphang S, Chanokkhun T, Muangsan N, Warrit N, Traiyasut P, Barnes CH, Watthana S. 2026. Reproductive biology and pollination ecology of two edible Limnophila species in Thailand. Biodiversitas 27 (1): d270117. https://doi.org/10.13057/biodiv/d270117. Culturally important native Thai herbs are declining due to habitat disturbance, overharvesting, and environmental stressors, including the use of herbicides. Limnophila geoffrayi, a native aquatic edible herb, has been especially affected by herbicide use and climate-driven rainfall anomalies. In contrast, the exotic Limnophila aromatica, introduced for edible herb usage, is widely vegetatively propagated. Both edible Limnophila species have poorly studied reproductive biology, which is important for native species conservation. The purpose of this study is to investigate the reproductive biology and pollination of the Thai native species L. geoffrayi to support conservation efforts, as well as to compare these traits to those of the introduced cultivated species, L. aromatica. Flowers of both species typically open for one day, with some L. geoffrayi flowers reopening on a second day. Diurnal opening and closing patterns corresponded with peak visitor activity. Solitary bees were the dominant pollinators, with 47.06% Sorensen’s similarity index of visitors between the two plant species. Although both species exhibit floral traits conducive to self-pollination, L. aromatica failed to produce fruit under both natural and insect-excluded conditions, indicating self-incompatibility. In contrast, L. geoffrayi consistently set fruit in bagged treatments, demonstrating self-compatibility and autonomous self-pollination, which resulted from polinator scant. High fruit set under natural conditions suggests strong reproductive assurance in the native species. Field observations also confirmed that both species provided pollen resources for solitary bees, which may contribute to cross-pollination within populations. Due to self-incompatibility and clonal propagation, introducing diverse genotypes is necessary for the long-term cultivation of L. aromatica. As an autonomously self-pollinating species that produces many seeds, L. geoffrayi may serve as a potential adaptation or resilience mechanism in the face of habitat disturbance and herbicide use. Being an annual herbaceous plant with different color forms, seed banking is required to support its conservation and sustainable use.